2022
DOI: 10.1021/acsami.2c13852
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Adhesiveness Regulates Myofibroblast Differentiation from Vocal Fold Fibroblasts in a Bio-orthogonally Cross-linked Hydrogel

Abstract: Repeated mechanical and chemical insults cause an irreversible alteration of extracellular matrix (ECM) composition and properties, giving rise to vocal fold scarring that is refractory to treatment. Although it is well known that fibroblast activation to myofibroblast is the key to the development of the pathology, the lack of a physiologically relevant in vitro model of vocal folds impedes mechanistic investigations on how ECM cues promote myofibroblast differentiation. Herein, we describe a bio-orthogonally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…With an overarching goal of modeling vocal fold maturation, we exploited the inverse electron demand Diels-Alder reaction between s-tetrazine and strained alkenes to develop a bioorthogonal hydrogel platform that is cell adhesive, enzymatically degradable, and dynamically tunable, allowing user-directed matrix stiffening in a spatiotemporal manner in the presence of MSCs. Instead of using two different types of crosslinking reactions, [16,28] we utilized slow (Nb) and fast (Tz) dienophiles to facilitate 3D cell encapsulation, ensure close to 100% conjugation of RGD to the network [14] and enable matrix stiffening in a diffusioncontrolled manner without the need for additional reagents, catalysts, or environmental changes (pH or temperature) that are potentially detrimental to cells or interfere with normal cell functions. [13,[29][30][31][32][33] Because diffusion of HA-TCO through the crosslinked network is relatively slow, our platform closely mimics the gradual changes in matrix stiffness during tissue maturation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With an overarching goal of modeling vocal fold maturation, we exploited the inverse electron demand Diels-Alder reaction between s-tetrazine and strained alkenes to develop a bioorthogonal hydrogel platform that is cell adhesive, enzymatically degradable, and dynamically tunable, allowing user-directed matrix stiffening in a spatiotemporal manner in the presence of MSCs. Instead of using two different types of crosslinking reactions, [16,28] we utilized slow (Nb) and fast (Tz) dienophiles to facilitate 3D cell encapsulation, ensure close to 100% conjugation of RGD to the network [14] and enable matrix stiffening in a diffusioncontrolled manner without the need for additional reagents, catalysts, or environmental changes (pH or temperature) that are potentially detrimental to cells or interfere with normal cell functions. [13,[29][30][31][32][33] Because diffusion of HA-TCO through the crosslinked network is relatively slow, our platform closely mimics the gradual changes in matrix stiffness during tissue maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous work, RGD conjugation in the primary network is close to 100%. [14] The mechanical properties of various HA gels were analyzed macroscopically using a DMA and microscopically using a custom micromechanical tester. Under unconfined compression, nLP, mLP, and sLP gels exhibited an average compression modulus of 4.9 ± 0.6 kPa, 6.1 ±1.1 kPa, and 10.3 ± 3.0 kPa, respectively.…”
Section: Fast Tetrazine-tco Ligation Permits Spatiotemporal Tuning Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggested that MIR31 may co-function with the 17 collagen production regulators to play a role in the VFWH process. In addition, our study also showed that MIR31 was related to multiple biological processes that were linked to wound healing, including fibrosis and keloid [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the limitations of traditional hydrogels, researchers have explored complementary approaches that confer defined cell-guidance cues and spatiotemporal dynamic modulation. [30][31][32] Using modular and orthogonal design strategies, 33,34 natural polysaccharides and proteins found in ECM can be modified to generate hydrogel with defined chemical and mechanical environments. These engineered hydrogel platforms have been shown to allow for temporal monitoring of sequential cellular events during vascular morphogenesis and vascularization, establishing engineered microvasculature and perfusable capillary networks in vitro and in vivo.…”
Section: Hydrogel Platform In Microvascular Tissue Engineeringmentioning
confidence: 99%